Recent Advances in Indoor Localization Systems and Technologies - Simon, Gyula; Sujbert, László (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Despite the enormous technical progress seen in the past few years, the maturity of indoor localization technologies has not yet reached the level of GNSS solutions. The 23 selected papers in this book present the recent advances and new developments in indoor localization systems and technologies, propose novel or improved methods with increased performance, provide insight into various aspects of quality control, and also introduce some unorthodox positioning methods.